Does income inequality lead to terrorism? Evidence from the post-9/11 era - Tim Krieger; Daniel Meierreiks (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2015)
We study the influence of income inequality on terrorism. Using cross-national data for 79 countries for the 2002-2012 period, we show that endogeneity matters to the inequalityterrorism relationship, e.g., because of the distributional effects of terrorism. Once endogeneity is properly accounted for by means of an instrumental-variable approach, higher levels of income inequality result in more terrorist activity. This finding is robust to different definitions of the dependent variable, different estimation techniques and different instruments for income inequality. Our finding that inequality fuels terrorism is consistent with relative deprivation theory which argues that conflict results from frustration over the actual distribution of economic resources within a society.
Keywords: C36; D74; 330; income inequality; terrorism; Gini coefficient; instrumental-variable approach